Perspectives On Using Pilis For Holistic Healing During Postpartum Period - Soraya, Desi; Vallen IP , Nella (Pusat Riset dan Inovasi Nasional, 2024)
All Indonesian people who utilize traditional health services are motivated by history, living environment, and customs. During postpartum many mothers experience anxiety that has no known cause, so in reducing anxiety pilis is given as a therapy that is believed to provide calmness in postpartum mothers. If they do not use pilis, the Javanese community believes that there will be sawanan in postpartum mothers and their babies. The purpose of this study was to describe the perspective of using pilis in the holistic healing process of the postpartum period. This research uses a qualitative descriptive method with phenomenological studies. Researchers conducted interviews by revealing holistic healing of postpartum mothers in the Javanese tribe using pilis in Demak Regency. This research was conducted in the working area of the Mranggen II Health Center, Demak Regency, which still uses pilis on postpartum women. The technique of determining informants using accidental sampling. The community's perspective with pilis treatment for postpartum women can provide a sense of calm and relaxation to the mother, nourish the body, especially in reducing stress during postpartum due to lack of rest. Pilis treatment based on local wisdom, family, and community is used because the ingredients are easily available and the price is more economical compared to the use of modern medicine.